2017
DOI: 10.1016/j.jad.2017.03.035
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal association between self-injurious thoughts and behaviors and suicidal behavior in adolescents and young adults: A systematic review with meta-analysis

Abstract: Although more than two thirds of suicide deaths in adolescence/young adulthood have occurred with no previous suicidal behavior, previous SITBs have a much higher risk of dying by suicide than previously reported in this age group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
106
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 209 publications
(116 citation statements)
references
References 49 publications
4
106
1
5
Order By: Relevance
“…The World Health Organization considers suicide a major public health issue and has emphasised the importance of targeting new suicide prevention approaches to individuals and groups who are at particular risk of suicide [5,6]. Given that depressive disorders [7] and history of suicidal ideation and behaviour [8] are among the strongest predictors of future suicidal behaviour, there is a need for targeted suicide prevention approaches to support young people exhibiting these risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization considers suicide a major public health issue and has emphasised the importance of targeting new suicide prevention approaches to individuals and groups who are at particular risk of suicide [5,6]. Given that depressive disorders [7] and history of suicidal ideation and behaviour [8] are among the strongest predictors of future suicidal behaviour, there is a need for targeted suicide prevention approaches to support young people exhibiting these risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…There is abundant literature on risk factors associated with suicidal behaviour. These include prior presence of suicidal behaviour ; exposure to traumatic stressful events, such as abuse or victimization; the existence of some legal factors ; certain psychological factors, such as hopelessness, impulsiveness, or low self‐esteem ; the presence of somatic or disabling problems ; or previous history of mental disorders, especially emotional (depression and anxiety) and behavioural disorders .…”
Section: Introductionmentioning
confidence: 99%
“…Non-suicidal self-injury (NSSI), as a growing health concern around the world, has been increasingly common in individuals with no mental illness, especially among adolescents and university students (Hawton et al 1997, White-Kress et al 2004. A recent meta-analysis study with a systematic review showed that adolescents who have self-injurious thoughts and behaviors had a two-fold risk of dying by suicide (Castellvi et al 2017).…”
Section: Introductionmentioning
confidence: 99%